2020
DOI: 10.1111/xen.12584
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of rat‐to‐mouse islets xenograft survival by co‐transplantation of autologous IL‐10 differentiated murine tolerogenic dendritic cells

Abstract: Background Tolerogenic dendritic cells (DCs) represent a promising approach to promote transplantation tolerance. In this study, the potential of autologous bone marrow (BM)–derived murine DC to protect rat‐to‐mouse islets xenografts was analyzed. Methods Tolerogenic DCs were generated by differentiating BM cells in the presence of granulocyte‐macrophage colony‐stimulating factor and interleukin 10 (IL‐10, IL‐10 DC). The phenotype of IL‐10 DC was characterized in vitro by expression of costimulatory/inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Prolonged xenograft survival of rat islets in diabetic mice was observed after an autologous IL-10-pulsed DC administration without any immunosuppressive treatment. The injection of IL-10-pulsed DC enriches graft infiltrating regulatory CD8 + T cells and tolerogenic myeloid cells with suppression-associated phenotypes ( 80 ). DC cotransfected Fas-L and IL-10 have more capacity to inhibit T cell activation and prolong the survival period of allografts than Fas-L alone ( 94 ).…”
Section: The Function Of Tol-dcmentioning
confidence: 99%
“…Prolonged xenograft survival of rat islets in diabetic mice was observed after an autologous IL-10-pulsed DC administration without any immunosuppressive treatment. The injection of IL-10-pulsed DC enriches graft infiltrating regulatory CD8 + T cells and tolerogenic myeloid cells with suppression-associated phenotypes ( 80 ). DC cotransfected Fas-L and IL-10 have more capacity to inhibit T cell activation and prolong the survival period of allografts than Fas-L alone ( 94 ).…”
Section: The Function Of Tol-dcmentioning
confidence: 99%
“…Madelon et al. proved that co-transplantation of autologous IL-10 treated murine tolerogenic DCs enhanced the rat islet xenograft survival in diabetic mice ( 53 ). One group in 2018 demonstrated that NHP derived tolerogenic DCs could induce the porcine-specific Tregs ( 54 ).…”
Section: Advanced Immunosuppression Protocols For Xenotransplant Trialsmentioning
confidence: 99%
“…Ezzelarab et al infused donor-derived tolerogenic DCs processed by vitamin D3, IL-10 into rhesus macaque models, showing that graft survival prolonged with no evidence of host sensitization (124). Autologous tolerogenic DC infusion could also lengthen the survival time of grafts, and murine IL-10-induced DCs can function as rejection inhibitors in vivo and in vitro expressing lower levels of MHCII, CD40, CD86, CD205 (125)(126)(127).…”
Section: Tolerogenic Dcs Possible Anti-rejection Effectsmentioning
confidence: 99%